Effect of Resistance Training with the Push, Pull, and Leg Method on Increasing the Volume Oxygen Maximal Uptake (VO2 Max) - Andrie Suryanta; dr. Su Djie Rante, Sp.OT (K); dr. Derri R. Tallo Manafe, M.Sc; dr. Regina M. Hutasoit, M.Kes (Universitas Nusa Cendana, 2025)
Over the past three decades there have been many studies that have shown that low levels of cardiorespiratory fitness are associated with an increased risk of cardiovascular and all-cause mortality. One way to improve cardiorespiratory fitness is to increase exercise, where resistance training is one of the exercises that can be done. The best way to measure cardiorespiratory fitness is by measuring the value of (VO2 max). To determine the effect of resistance training on increasing VO2 max. The type of research conducted was quasi experimental with a pretest and posttest non equivalent design approach. The research was conducted on students of the Seminar Biara Hati Kudus with 40 respondents, who were divided into two groups, namely the treatment and control groups. There was a significant increase in VO2 max value with p=0.000 in the treatment group. However, there was no significant increase with a value of p=0.249 in the control group. There were also significant results when comparing posttest values between the treatment and control groups with a value of p = 0.036. Resistance training with the push, pull, and leg method three times a week for three weeks can affect the increase in VO2 max.